The effect of topical thiocolchicoside in preventing and reducing the increase of muscle tone, stiffness, and soreness: A real-life study on top-level road cyclists during stage competition. Issue 30 (July 2017) - Gervasi, Marco; Sisti, Davide; Benelli, Piero; Fernández-Peña, Eneko; Calcabrini, Cinzia; Rocchi, Marco B.L.; Lanata, Luigi; Bagnasco, Michela; Tonti, Andrea; Vilberto, Stocchi; Sestili, Piero
Abstract : Abstract: In professional road cyclists, the majority of overuse injuries affect the lower limbs and are mostly represented by contractures or muscle shortening, characterized by an increase of tone and stiffness and a variation of elasticity. Treatment and prevention of these specific conditions may include physical, supplementary, and pharmacologic support. The aim of this real-life study was to determine: first, the alterations of tone, stiffness, elasticity, and soreness of rectus femoris (RF) and biceps femoris (BF) in top class cyclists engaged in 3 multistage races, and second, whether any variable in the management of the athletes may affect the prevention and/or reduction of such alterations. Twenty-three professional cyclists competing in 3 international, cycling stage races were assessed. Athletes could receive, upon the approval of the medical staff, physical, dietary, and/or pharmacological management which could include treatments with topical over-the-counter myorelaxants to prevent and/or reduce muscle contractures. MyotonPro was used to daily measure tone, stiffness, and elasticity in RF and BF in relaxed and contracted state after every stage. In parallel, BF and RF soreness was also assessed with a Likert scale. All athletes received the same general massage management; none of them received dietary supplements; some of the athletes were treated with a topical myorelaxant thiocolchicoside (TCC 0.25%) foam 3 times daily. TCC was identified as the only variable able to affect these muscle parameters in the cyclists. Tone, stiffness (regardless of the state), and soreness significantly increased over time either in BF or RF in all athletes. In the group of athletes that used TCC (n = 11; TCC+) the increase in tone, stiffness, and soreness was significantly lower than in the group not receiving TCC (n = 12; No-TCC). Elasticity varied coherently with tone and stiffness. A very intense and protracted sport activity increases muscular tone, stiffness, and soreness over time. Topical TCC foam significantly attenuates these alterations and might represent an efficient strategy both to prevent and manage contractures and their consequences in professional cyclists as well in athletes from other disciplines involving similar workloads.